Here is your system of equations:
![\left \{ {{2x+3y=-6} \atop {3x-4y=-12}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/26clr9tkdjmg1z2lwh38ml1pbldxm0wxno.png)
When solving a system, you can either substitute or eliminate. I am going to eliminate because you can only substitute when there are answer choices.
When eliminating, you need either x or y to be the same or opposite(sign). I am going to eliminate y, whuch means 3y and -4y has to have the same number. To make them the same, I will multiply the two numbers because multiplying two numbers is an easier way to find a common multiple.
![3 * 4 = 12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lvcxaa2ornkda8ieiazmrzd58rbdpztnnb.png)
That means they both have to be changed so that their value is 12.
![2x+3y=-6 \\ \\ 3 * ?=12 \\ ?=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k4qcn41n4ymwlpfyfbqhohzdrred1z0hqs.png)
You have to multiply the first equation by 4.
![2x+3y=-6 \rightarrow 8x+12y=-24](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5sa5m4kjpo5shm7drrsf73ukme8upk2vku.png)
For the second equation, I will have to multiply by 3 because:
![3x-4y=-12 \\ \\-4 * ?=-12 \\?=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6tbcqo3437xntdwcpb0o2qv2mjuj1kncls.png)
Multiply the second equation by 3:
![3x-4y=-12 \rightarrow 9x-12y=-36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vht14elwvxpejqsj2s6o2x0qkmbd4zlpp5.png)
Here is your new system of equations:
![\left \{ {{8x+12y=-24} \atop {9x-12y=-36}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p7l45nmd0149bo4hkpdyjo4yn0i63hyctn.png)
Add:
![{8x+12y=-24} \\{9x-12y=-36} \\ \\ 17x=-60](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u1hroxy3vvbcoe9zn069rpslezq3ir4sm6.png)
y is eliminated because when a number is added/subtracted by its opposite, it's cancelled out.
Although the case is different, remember:
NEGATIVES
- Negative(-) times(×) negative(-) = positive(+)
- Negative(-) times(×) positive(+) = negative(-)
- Negative(-) divided(÷) by positive(+) = negative(-)
- Negative(-) divided(÷) by negative(-) = positive(+)
POSITIVES
- Positive(+) times(×) positive(+) = positive(+)
- Positive(-) times(×) negative(-) = negative(-)
- Positive(+) divided(÷) by positive(+) = positive(+)
- Positive(+) divided(÷) by negative(-) = negative(-)
Now you need to divide both sides by 17 to leave x alone.
![(17x)/(17) =(-60)/(17) \\ \\ x=-(60)/(17)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q8qhfu7fpeqopk4b5z54n2bf6mvk7u3tel.png)
Since x has a value, that means y also does. That also means the answer to your question is one solution.